The Impact of Work Environment Quality on Organizational Conflict Management: "An Exploratory Study in Balad Public Hospital" - Abdulrazak, Khansaa Mohammed Hassan; Abdulhussien, Safaa Jawad (Journal of Techniques, 2022)
This research aims to analyze the impact of the quality of the work environment in managing organizational conflict in Balad General Hospital. This includes studying the impact of the current working conditions on the functional work carried out by employees on the material and moral sides. The work environment quality was performed as an independent variable. While the management of organizational conflict was a dependent variable. This study was applied in Balad General Hospital. That achieves the objectives and hypotheses of this research. The research problem indicates there is a lack of a comfortable work environment that enables employees to perform their tasks with a high quality، which led to an increase in organizational conflict in the research sample. A random sample was selected (140) of the staff in the different level departments like heads of medical departments، doctors، nurses، administrators and supervisors of medical activities. Which represents part of the study population of (220). Data collected by using interview staff and survey questionnaire. A descriptive analytical method based on the statistical program (SPSS V. 24) was used to analyze this data. This methods like mean، standard deviation، coefficient of variation، spearman’s correlation coefficient and simple linear regression. The results approved there is a significant correlation between the the quality of the work environment and the management of organizational conflict. Therefore، the hospital management needs to improve the quality of the work environment so that it is compatible with the medical working conditions. Which contribute to avoiding and reducing the proportion of organizational conflicts between employees. Accordingly، this study proposes to enhance the dimensions of the low level of quality specifications required in the work environment from the design of offices، buildings، and staff comfort requirements.